News Briefs. (Computer (00189162), 2014)
Topics include the US giving up administrative control of the Internet, journalists facing increasing attacks from hackers, Sony's virtual-reality gaming headset, a drone that could steal data from smartphones, a project that aims to build mobile networks cheaply, a new deep-learning system for smartphones, smart homes being easy targets for hackers, content providers challenging ISPs over slow network speeds, a Qualcomm technology that promises to triple Wi-Fi speeds, and a social app that helps users avoid people they don't want to see.